2014
DOI: 10.1021/bi401568a
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Gatekeeper and Controlled Assembly of Trpzip β-Hairpins

Abstract: Protein and peptide aggregation is an important issue both in vivo and in vitro. Herein, we examine the aggregation behaviors of two well studied β-hairpins, Trpzip1 and Trpzip2. Previous studies suggest that Trpzip2 remains monomeric up to a concentration of ~15 mM whereas Trpzip1 readily aggregates at micromolar concentrations at acidic or neutral pH. This disparity is puzzling considering that these two peptides only differ in their turn sequences (i.e., GN versus NG). We hypothesize that these peptides can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…We chose the denomination "aggregation gatekeepers" rather than "structural gatekeepers" to emphasize the specific position of these residues at the flanks of APRs. Several other studies confirmed the prevalence and importance of the GK pattern (Monsellier et al, 2008;Tartaglia & Vendruscolo, 2008;Buell et al, 2009;Wang et al, 2010b;Markiewicz et al, 2014;Sant'Anna et al, 2014;Estácio et al, 2015). We later confirmed that GKs constitute a bona fide and ubiquitous functional class specifically devoted to protein homeostasis.…”
Section: Introductionsupporting
confidence: 78%
“…We chose the denomination "aggregation gatekeepers" rather than "structural gatekeepers" to emphasize the specific position of these residues at the flanks of APRs. Several other studies confirmed the prevalence and importance of the GK pattern (Monsellier et al, 2008;Tartaglia & Vendruscolo, 2008;Buell et al, 2009;Wang et al, 2010b;Markiewicz et al, 2014;Sant'Anna et al, 2014;Estácio et al, 2015). We later confirmed that GKs constitute a bona fide and ubiquitous functional class specifically devoted to protein homeostasis.…”
Section: Introductionsupporting
confidence: 78%
“…In addition to the aforementioned amyloidogenic proteins, the backbone amide I spectra have been widely used in aggregation studies of other disease-associated amyloidogenic proteins, e.g., crystallin [83], prion [84,85], polyglutamine (polyQ) [86], and model peptides [87,88]. For instance, deposits of aggregated crystallin on the lens of the eye cause blurred vision or blindness in cataracts.…”
Section: Backbone Vibrational Probementioning
confidence: 99%
“…In this PEGylated tetra‐peptide the Phe residue was replaced with the tryptophan (Trp, W). W is one of the essential amino acids and the aromatic ring in its side chain can represent fruitful chemical tool to address the aggregation in short peptides sequences . In addition, it is well‐known that Trp in long peptides or proteins can create structural motifs, called tryptophan zippers (Trpzip), which are stabilizing elements for the β‐hairpin conformation .…”
Section: Introductionmentioning
confidence: 99%
“…W is one of the essential amino acids and the aromatic ring in its side chain can represent fruitful chemical tool to address the aggregation in short peptides sequences. [30] In addition, it is well-known that Trp in long peptides or proteins can create structural motifs, called tryptophan zippers (Trpzip), which are stabilizing elements for the b-hairpin conformation. [31] Indeed, analogously to the previously studied PEG 6 -F4, also PEG 6 -W4 possesses a high tendency to aggregate.…”
Section: Introductionmentioning
confidence: 99%